ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN PENJUMLAHAN BERSUSUN DI SD NEGERI 27 KOTA SORONG: ANALYSIS OF ELEMENTARY SCHOOL STUDENTS' DIFFICULTIES IN SOLVING MULTIPLE ADDITION - Mahendra, Faisal Eka; Phricilia, Regina; Anwar, Zakiyah; Sulistyowati, Fitria; Rumalean, Lismawati (KAMBIK: Journal of Mathematics Education, 2025)
This study aims to analyze and identify the types of difficulties experienced by third-grade students of SD Negeri 27, Sorong City, in solving compound addition problems. Data collection was conducted using test sheets and observations of 25 students. Based on the analysis, it was found that student errors can be classified into five categories, namely: errors in understanding concepts (20%), errors in understanding questions (32%), errors in the process transformation stage (16%), errors in process skills (12%), and errors in writing the final answer (20%). Errors in understanding questions were the most dominant, while errors in process skills had the lowest percentage. The main factors causing difficulties include a lack of understanding of basic concepts, inaccuracy, and weak arithmetic skills. To overcome this problem, it is recommended to use visual learning media, gradual exercises, and reinforcement of basic concepts through a more interactive approach. This approach is expected to improve student understanding and reduce errors in solving compound addition problems.